2005
DOI: 10.1002/fut.20185
|View full text |Cite
|
Sign up to set email alerts
|

Structurally sound dynamic index futures hedging

Abstract: Portfolio managers use index futures for a variety of reasons. Regardless of their motivation, they will keep a close eye on the relation between the index futures returns and their stock-portfolio returns. Whenever this relation is perceived to have changed, the manager will decide whether it is worthwhile to rebalance the index futures-portfolio mix accordingly. Exact measures as to when and how much rebalancing should occur have not yet been established. This article proposes a dynamic hedging algorithm bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In order to mitigate the effect of illiquidity on hedging, hedgers hedge through near to expiry futures contract and roll the position to next contract to achieve long-term hedging objectives (Neuberger, 1999;Telser, 1981). On the same lines of hypothesis, Harris and Shen (2003) and Kofman and McGlenchy (2005) have suggested that time varying hedge ratio estimated through GARCH family models provides statistically and economically better hedge ratio as compared to other models. They have tested rolling window methodology to get these results.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to mitigate the effect of illiquidity on hedging, hedgers hedge through near to expiry futures contract and roll the position to next contract to achieve long-term hedging objectives (Neuberger, 1999;Telser, 1981). On the same lines of hypothesis, Harris and Shen (2003) and Kofman and McGlenchy (2005) have suggested that time varying hedge ratio estimated through GARCH family models provides statistically and economically better hedge ratio as compared to other models. They have tested rolling window methodology to get these results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2.For further information, see Kroner and Sultan (1993), Park and Switzer (1995), Lien and Tse (1998), Harris and Shen (2003), Yang and Allen (2004), Kofman and McGlenchy (2005), Floros and Vougas (2004), Bhaduri and Durai (2007), and Lee and Yoder (2007). …”
mentioning
confidence: 99%
“…Finally, the presence of significant asymmetric effects should be noted for the SP500 as [as in Kroner and Sultan (1993), Lee et al (2006) and Kofman and McGlenchy (2005) …”
Section: The Bivariate Garch Modelmentioning
confidence: 99%
“…However, it is a well-established fact that a financial time series observes time varying patterns, and that volatility clustering is their innate feature (Gupta and Singh, 2009). Hence, voluminous literature has found that time-varying hedge ratios are superior to constant hedge ratios (Myers, 1991;Park and Switzer, 1995;Aggarwal and Demaskey, 1997;Moschini and Myers, 2002;Harris and Shen, 2003;Pattarin and Ferretti, 2004;Kofman and McGlenchy, 2005;Floros and Vougas, 2006;Bhaduri and Durai, 2007;Yoder, 2007 andYang andLai, 2009). Furthermore, Yang and Allen (2004) confirmed that a time-varying hedge ratio performs better during out of sample hedging.…”
Section: Review Of Literaturementioning
confidence: 99%